Pengaruh Persepsi Manfaat, Kemudahan, dan Kenyamanan Terhadap Minat Penggunaan E-Payment (Qris) - Awotkay, Apolinaris S. (Sekolah Tinggi Ilmu Administrasi Karya Dharma, 2025)
QRIS as a payment method. Where it is seen in the campus environment, Bank BNI has implemented a payment system using QRIS with the aim of making it easier and more efficient for students to pay semester fees. In addition, on campus there is a canteen where several sellers have used QRIS as a payment method. The purpose of this study is to determine the effect of perceived benefits, ease, and convenience on the interest in using E-payment (QRIS). The type of research approach used in this study is a quantitative research method. The population in this study were students of the Faculty of Economics and Business, class of 2020 and 2021, totaling 698 students with a sample size of 88 respondents. The sampling technique used in this study was non-probability sampling with purposive sampling. The results of this study indicate that the perception of benefits partially does not have a positive and significant effect on the interest in use. Convenience partially does not have a positive and significant effect on the interest in use. While convenience partially has a positive and significant effect on the interest in use. The results of the F test based on the data results showed that the perception of benefits, ease, and convenience simultaneously had a positive and significant effect on the interest in use.